Bombeamento de água utilizando sistema fotovoltaico autônomo : um estudo de caso - Magalhães, Graziela Esteves (2016)
In Sinop-MT municipality region is common to use CA centrifugal motor pumps of low power to raise water cisterns or wells of small depth to reservoir located usually about three meters above the ground, the height of the roofs of buildings, to meet the daily needs of water consumption of users. This work aims at the establishment of an autonomous photovoltaic pumping system using pump of low power DC coupled directly to the PV panel. This alternative aims to reduce dependence on the consumer of the water supply company and electric utility in situations of lack of water or electricity supply. It should expose the municipal water supply study is done by direct pumping of artesian wells scattered throughout the city's neighborhoods, using no water tank. The method chosen to evaluate the proposed pumping system was experimental, through case study. The stand-alone photovoltaic pumping system implemented uses underground water from a tube well in shallow, home to meet the consumption needs of the building, inhabited by a family composed of four people. The system design considers the average values of radiation of the region and the daily consumption of water for a series of three days. Determine the head height, the capacity of the upper water reservoir according to the daily consumption, the voltage generated is monitored by the photovoltaic panels, current and power consumed by the pump. The implanted system must meet user needs, provide economy of electric power and autonomy of the electric utility and water supply.